Geneology of Astronomy Science In Java - Muammar Muammar; Muslich Shabir; Muhammad Falih Abdul Ghoni (Jurnal Hikmatuna, 2020)
This research will trace the process of transmission of falak science in Java from its inception to its current development: the geneology and the process of transmitting astronomy and developed pattern in Java. This research is a qualitative descriptive study with a historical approach. The steps taken are collecting data from the object under study (heuristic), verifying or criticizing the source, and making conclusions and interpreting existing authentic data. The analytical method used is descriptive analysis. The results showed that at the beginning of its development, the science of astronomy was studied and developed by Syekh Abdurrahman bin Ahmad al-Mishri al-Batawi who was then taught to Habib Usman al-Batawi, Sheikh Abdul Hamid al-Dumairi al-Batawi, and KH. Ahmad Dahlan as-Samarani. From here the science of astronomy developed and gave birth to a number of works including Tadzkirah al-Ikhwan, and Bulugh al-Wathar. The development of astronomy is then carried out through educational institutions both formal and informal. For formal education through tertiary institutions and informal through Islamic boarding schools.